2021
DOI: 10.1371/journal.pone.0250567
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in multimorbidity and polypharmacy trends: A repeated cross-sectional study of older adults in Ontario, Canada

Abstract: Background Multimorbidity is increasing among older adults, but the impact of these recent trends on the extent and complexity of polypharmacy and possible variation by sex remains unknown. We examined sex differences in multimorbidity, polypharmacy (5+ medications) and hyper-polypharmacy (10+ medications) in 2003 vs 2016, and the interactive associations between age, multimorbidity level, and time on polypharmacy measures. Methods and findings We employed a repeated cross-sectional study design with linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 45 publications
3
32
0
1
Order By: Relevance
“…The few studies that have focused on chronic disease in relation to polypharmacy have generally been performed in specific chronic disease populations [10]. In the overall population, and particularly among older patient groups, chronic disease has been shown to be a significant risk factor for polypharmacy [9].…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…The few studies that have focused on chronic disease in relation to polypharmacy have generally been performed in specific chronic disease populations [10]. In the overall population, and particularly among older patient groups, chronic disease has been shown to be a significant risk factor for polypharmacy [9].…”
Section: Plos Onementioning
confidence: 99%
“…Although prevalence increases substantially with age, in absolute terms multimorbidity is much more common in those aged 65 years or less [8,9]. Some studies have indicated interactive associations between sex, age and multimorbidity, which may depend on medical, lifestyle and social factors influencing the health status of patients [8,10]. Data on the age at which multimorbidity begins and how it evolves over time are urgently needed in order to develop focused interventions that help prevent multimorbidity and associated adverse health outcomes [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations